Kajian Komposisi dan Stratifikasi Tanaman Hortikultura Sebagai Penyusun di Ruang Terbuka Hijau (RTH) Taman Sritanjung Banyuwangi - Tristi Indah Dwi Kurnia (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2021)
The objectives of this study were (1) to determine the composition of the types of horticultural plants used as constituents in the green open space of Taman Sritanjung Banyuwangi and (2) to determine the canopy stratification pattern of horticultural plants in the Green Open Space (GOS) of Taman Sritanjung Banyuwangi. The method of determining the location of the research used is the purposive method, namely GOS Taman Sritanjung Banyuwangi. The research data were obtained by usingÂ  the line line census method, namely all plants in GOS that followed the line line were used as research samples. The data obtained were analyzed descriptively qualitatively. The results showed that (1) the composition of horticultural plants that make up of GOS consists 33 types of plants with function as shade plant (5 types), absorbers pollutions (4 types), noise absorbing plant (4 types), wind breakers (6 types), plant barrier, guide and form of views (7 types), conservation plant, and cover crops (8 types), and (2) In terms of stratification, horticultural plants selected as constituents in Sritanjung Banyuwangi GOS can be grouped into Emergent Layers, Canopy Layers, Lower Canopy, Shrubs and Ground CoverÂ Keywords: Composition, Stratification, GOS